Empowering MSMEs Through Social Media Marketing Training as an Effort to Increase Self-Efficacy and Product Sales Performance - Bobby Reza; Ronald Parulian; Sri Sukartono (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic development, particularly in developing countries. However, many MSMEs still face challenges in marketing their products effectively, especially in the digital era. One of the strategies to overcome this challenge is through social media marketing training that equips entrepreneurs with digital marketing skills and confidence in managing online businesses. This study aims to examine the role of social media marketing training in improving MSME self-efficacy and product sales performance. The research uses a descriptive and analytical approach with MSME participants involved in digital marketing training programs. The findings indicate that training in social media marketing significantly enhances entrepreneurs’ self-efficacy in managing online promotion, creating digital content, and interacting with consumers. Increased self-efficacy subsequently contributes to improved product visibility, customer engagement, and sales performance. Therefore, strengthening digital marketing competencies through structured training programs is essential for empowering MSMEs and enhancing their competitiveness in the digital economy.